PECULIARITIES OF INTERACTIVE HISTORY TEACHING AT HIGHER EDUCATIONAL INSTITUTIONS - Наталія Ігнатенко (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The problem of modernization of contemporary methods of teaching History at higher educational intitutions on the basis of innovative pedagogy has been studied. The peculiarities of interactive teaching technology application as a means of activation and intensification of students' cognitive activity while studying History at higher educational intitutions have been analyzed. The purpose, tasks and dedactic peculiarities of interactive teaching technology application in higher educational insitutions have been characterized. The methodology of History lessons structuring in the system of interactive teaching and the specifics of application of interactive teaching methods and techniques in History teacher training have been researched. Tadvantages of interactive teaching in terms of the paradigm of new pedagogical technologies have been substantiated.